Plasticity in gas‐exchange physiology of mature Scots pine and European larch drive short‐ and long‐term adjustments to changes in water availability. (September 2017) - Feichtinger, Linda M.; Siegwolf, Rolf T.W.; Gessler, Arthur; Buchmann, Nina; Lévesque, Mathieu; Rigling, Andreas
Abstract: Adjustment mechanisms of trees to changes in soil‐water availability over long periods are poorly understood, but crucial to improve estimates of forest development in a changing climate. We compared mature trees of Scots pine ( Pinus sylvestris ) and European larch ( Larix decidua ) growing along water‐permeable channels (irrigated) and under natural conditions (control) at three sites in inner‐Alpine dry valleys. At two sites, the irrigation had been stopped in the 1980s. We combined measurements of basal area increment (BAI), tree height and gas‐exchange physiology (Δ 13 C) for the period 1970–2009. At one site, the Δ 13 C of irrigated pine trees was higher than that of the control in all years, while at the other sites, it differed in pine and larch only in years with dry climatic conditions. During the first decade after the sudden change in water availability, the BAI and Δ 13 C of originally irrigated pine and larch trees decreased instantly, but subsequently reached higher levels than those of the control by 2009 (15 years afterwards). We found a high plasticity in the gas‐exchange physiology of pine and larch and site‐specific responses to changes in water availability. Our study highlights the ability of trees to adjust to new conditions, thus showing high resilience. Abstract : We studied long‐term responses of mature Scots pine and European larch trees towards changes in water availability, taking advantage of historical irrigation channels. With the assessment of radial growth and stable carbon isotopes, we were able to link tree physiology and performance with water availability over a time period of up to 40 years. We found a high plasticity in the gas‐exchange physiology and site‐specific responses to changes in water availability. Our work emphasizes the importance to simultaneously consider short‐term responses and long‐term adjustments of trees to drought when assessing forest responses to global environmental changes.